An evaluation of the clinical features of measles virus infection for diagnosis in children within a limited resources setting - Dominicus Husada; Kusdwijono; Dwiyanti Puspitasari; Leny Kartina; Parwati Setiono Basuki; Ismoedijanto (BMC, 2020)
Abstract Background Measles is a recurrent health problem in both advanced and developed countries. The World Health Organization (WHO) recommends anti-measles immunoglobulin M (Ig M) as the standard method of detecting the virus; however, many areas still present the inability to perform a serology test of anti-measles IgM. Therefore, a typical clinical feature is necessary to establish the diagnosis of measles. The objective of this study was to evaluate hyperpigmented rash and other clinical features as the diagnostic tools with respect to measles, especially in an outbreak setting. Methods In this observational diagnostic study, the inclusion criteria were as follows: between 6 and 144 months of age, fever, maculopapular rash for 3 days or more, accompanied by a cough, or coryza, or conjunctivitis. Those with a prior history of measles vaccination (1-6 weeks) were excluded, in addition to those with histories of corticosteroid for 2 weeks or more and immunocompromised conditions. The samples were taken from Dr. Soetomo General Academic Hospital in Surabaya, Indonesia. We evaluated the sensitivity, specificity, the positive predictive value, and the negative predictive value of such clinical features. Hyperpigmented rash was validated using Kappa and Mc Nemar tests. Anti-measles Ig M was considered as the gold standard. Results This study gathered 82 participants. The clinical manifestations of all subjects included fever, cough, coryza, conjunctivitis, Koplik spots, and maculopapular rash (which turns into hyperpigmented rash along the course of the illness). Most maculopapular rashes turn out to be hyperpigmented (89%). Sensitivity, specificity, positive predictive value, and negative predictive values ​​of the combination of fever, maculopapular rash, and hyperpigmented rash were found to be at 90.7, 28.6, 93.2, and 22.2%, respectively. The Mc Nemar and Kappa tests showed p values of 0.774 and 0.119, respectively. Conclusion The combination of fever, maculopapular rash, and hyperpigmented rash can be used as a screening tool regarding measles infection in an outbreak setting, which can then be confirmed by anti-measles Ig M. Cough, coryza, and Koplik's spot can be added to this combination, albeit with a slight reduction of sensitivity value.